2019
DOI: 10.1177/1708538119847392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of side-to-end vs. side-to-side proximal arteriovenous fistula anastomosis in chronic renal failure patients

Abstract: Introduction Anastomotic creation of autogenous arteriovenous fistulas can be performed in different ways, side-to-end or side-to-side. However, there is a paucity of evidence to recommend them. The aim of this study is to compare both anastomosis types in elbow arteriovenous fistulas. Material and methods A prospective observational national multicenter study (ISRCTN62033470) was designed, including patients receiving a native arteriovenous fistula in the elbow using side-to-end or side-to-side anastomosis, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Thus, it can be concluded that the better patency noted with STS at 12 months in the combined meta-analysis of all studies was influenced by distal vein ligation. These results are similar to another recent meta-analysis of Weigang et al (21) which too noted better patency rates with STS and distal vein ligation but with just seven studies in the review.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, it can be concluded that the better patency noted with STS at 12 months in the combined meta-analysis of all studies was influenced by distal vein ligation. These results are similar to another recent meta-analysis of Weigang et al (21) which too noted better patency rates with STS and distal vein ligation but with just seven studies in the review.…”
Section: Discussionsupporting
confidence: 90%
“…All studies were thoroughly screened to identify 23 articles related to the review topic. Seven studies were excluded and 16 studies were analyzed in our systematic review and meta-analysis (8)(9)(10)(11)(12)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations